IMPLEMENTASI MANAJEMEN SEKOLAH BERDASARKAN ACUAN AKREDITASI SATUAN PENDIDIKAN DI SEKOLAH DASAR - Fitriani Afrilia Nur Jufri; Wahira Wahira (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This study examines the implementation of school management based on school accreditation references. the focus of this research is to determine the achievement of school management components at Integral Al Bayan Makassar elementary school. The purpose of this study was to determine the achievement of school management components at Integral Al Bayan Makassar elementary school. The approach in this research is qualitative with descriptive approach. This research was conducted at Al Bayan Makassar Integral Elementary School. The data sources in this study were principals and teachers. Data collection techniques are observation, interview and documentation. Data analysis techniques use data reduction, data presentation and conclusion drawing. Checking the validity of the data using triangulation techniques. The results showed that the implementation of school management based on school accreditation reference includes: (1) Curriculum Management, In curriculum management, Al Bayan Makassar Integral Elementary School involves stakeholders continuously in curriculum development to meet the target of quality excellence in curriculum development, involves stakeholders to adjust programs based on needs and provides a budget for curriculum implementation. (2) Management of Teachers and Education Personnel, Al Bayan Makassar Integral Elementary School in the management of teachers and education personnel by first recruiting teachers and education personnel in accordance with the criteria, recruitment and selection that is transparent and accountable conducted by the foundation and then new teachers and education personnel will be coached and assisted at school for three months. (3) Management of Facilities and Infrastructure, Management of facilities and infrastructure at Al Bayan Makassar Integral Elementary School has a positive impact on the learning process, schools always ensure that all facilities and infrastructure are ready for use by checking regularly so as not to interfere with the entire educational process at school, schools also always observe if there are obstacles or deficiencies in the availability of facilities and infrastructure.